Approaching an overdamped system as a quadratic eigenvalue problem - Forjaz, Maria Antónia (2017)
In viscous material systems,time and stress dependente instabilities often occur. The evolution of visco-elastic systems under external stress has already been modeled by applying a matricial dynamics equation comprehending elasticity and viscosity matrices. In this study we report a novel formulation for such kind of systems in an overdamped regime as a nonlinear quadratic eigenvalue problem. The results presented were obtained after solving the eigenvalue equation of several sets of discrete damped mass-spring systems.